2021
DOI: 10.3389/fpsyt.2021.765106
|View full text |Cite
|
Sign up to set email alerts
|

Use of Transcutaneous Auricular Vagus Nerve Stimulation as an Adjuvant Therapy for the Depressive Symptoms of COVID-19: A Literature Review

Abstract: The coronavirus disease 2019 (COVID-19) comprises more than just severe acute respiratory syndrome. It also interacts with the cardiovascular, nervous, renal, and immune systems at multiple levels, increasing morbidity in patients with underlying cardiometabolic conditions and inducing myocardial injury or dysfunction. Transcutaneous auricular vagus nerve stimulation (taVNS), which is derived from auricular acupuncture, has become a popular therapy that is increasingly accessible to the general public in moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 142 publications
0
11
0
Order By: Relevance
“…To the best of our knowledge, this is the first prospective randomised study using aVNS in patients with critical Covid-19. Although the potential positive impact of vagus nerve stimulation on cytokine storm in patients with severe Covid-19 was often discussed ( Bonaz et al, 2020a , 2020b ; Bara, de Ridder and Maciaczyk, 2020 ; Kaniusas and Szeles, 2020b ; Guo et al, 2021 ; Wang et al, 2022 ), clinical data is scarce. Boezaart et al reported two cases of patients with severe Covid-19 receiving transcutaneous aVNS in addition to standard of care in which case a rapid decrease of IL-6 was observed and aVNS was well tolerated ( Boezaart and Botha, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first prospective randomised study using aVNS in patients with critical Covid-19. Although the potential positive impact of vagus nerve stimulation on cytokine storm in patients with severe Covid-19 was often discussed ( Bonaz et al, 2020a , 2020b ; Bara, de Ridder and Maciaczyk, 2020 ; Kaniusas and Szeles, 2020b ; Guo et al, 2021 ; Wang et al, 2022 ), clinical data is scarce. Boezaart et al reported two cases of patients with severe Covid-19 receiving transcutaneous aVNS in addition to standard of care in which case a rapid decrease of IL-6 was observed and aVNS was well tolerated ( Boezaart and Botha, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of them are far from routine clinical practice such as immunopsychiatric strategies [51] or natural molecules such as luteolin or quercitin which appear promising and safe [55,56]. Use of transcutaneous auricular vagus nerve treatments could also help treat depressive symptoms with a good tolerance [58]. However, without any clinical trial, these therapeutics remain hypothetical and should be explored in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…This is derived from auricular acupuncture, widely used in China [57]. These authors suggest an efficacy of taVNS on post-COVID-19 depression that involves a cholinergic anti-inflammatory pathway and modulates brain circuits via the hypothalamic-pituitary-adrenal axis [58].…”
Section: Alternative Therapeutic Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent report has indicated that >87% of COVID-19 patients continue to experience at least one symptom following acute recovery (144), the most frequent of which was fatigue. Noninvasive brain stimulation approaches have reliable benefit for fatigue (145), as well as for psychological symptoms such as depression and anxiety that are common in the recovery period (146)(147)(148).…”
Section: Future Perspectivesmentioning
confidence: 99%